Smart Car Detector / Balqis Muhammad Adzhari - Muhammad Adzhari, Balqis (2020)
This company that registered under Companies Commission of Malaysia (SSM) as BFF Enterprise are company that involve in inventing new product that will give satisfaction and solve customer product. For the new product, this company have upgraded the uses of GPS for car user to smart car detector. This product help car user a lot prevent from accident and also protect the user. The product may detect any movement when it want to reverse, it will halt the car movement until no move detect. Other than that this product come with mini hidden camera and alarm. This mini hidden camera function as CCTV or as guide for the user to see what is at the back of their car. Meanwhile the alarm function as to detect danger which may harm the car or car user. It will rang once sharp or hard object touch the car body. This give customer an alert that their car in danger and may notify the others to help them. The alarm would stop once no harm detect. The product came with three highlight items which, movement detector, mini hidden camera and alarm. It is called smart detector altogether to let the user know that this product would not give burden to the user. For example if their alarm rang, user have to close the alarm on their own and disturb the others. The alarm stop o their own which prevent the car battery from losing the battery. It such a good product that give benefit to the others as this product affordable and can be used on any type of car.